Fixed Point Results of Dynamic Process Dˇϒ,μ0 through FIC-Contractions with Applications - Amjad Ali; Eskandar Ameer; Muhammad Arshad; Hüseyin Işık; Mustafa Mudhesh (Complexity)
This article constitutes the new fixed point results of dynamic process D(ϒ, μ0) through FIC-integral contractions of the Ciric kind and investigates the said contraction to iterate a fixed point of set-valued mappings in the module of metric space. To do so, we use the dynamic process instead of the conventional Picard sequence. The main results are examined by tangible nontrivial examples which display the motivation for such investigation. The work is completed by giving an application to Liouville‐Caputo fractional differential equations.